2023
DOI: 10.1227/neu.0000000000002306
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Utilization, Charges, and Reimbursement After the Affordable Care Act: Trends From 2011 to 2019

Abstract: BACKGROUND:An estimated 50 million Americans receive Medicare health care coverage. Prior studies have established a downward trend in Medicare reimbursement for commonly billed surgical procedures, but it is unclear whether these trends hold true across all neurosurgical procedures.OBJECTIVE:To assess trends in utilization, charges, and reimbursement by Medicare for neurosurgical procedures after passage of the Affordable Care Act in 2010.METHODS:We review yearly Physician/Supplier Procedure Summary datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The authors' results demonstrated that enrollment-adjusted utilization decreased by 12.1%, whereas reimbursement decreased by 4.6%. 7…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors' results demonstrated that enrollment-adjusted utilization decreased by 12.1%, whereas reimbursement decreased by 4.6%. 7…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been limited research into Medicare reimbursement trends for pituitary tumor surgery specifically, there have been a number of recent publications focused on analyzing trends in utilization, charges, and reimbursement of surgical procedures across a number of medical specialties. 7,[14][15][16][17][18][19][20] Within neurosurgery, a study Haglin et al 20 used the CMS Physician Fee Schedule Look-Up Tool to extract reimbursement data for each of the top 10 most used CPT codes in both spinal and cranial neurosurgeries. The investigators found that the average reimbursement for all procedures decreased by an average of 25.80% from 2000 to 2018 when adjusting for inflation.…”
Section: Discussion Prior Researchmentioning
confidence: 99%
See 3 more Smart Citations